2004
DOI: 10.1111/j.1365-2230.2004.01421.x
|View full text |Cite
|
Sign up to set email alerts
|

A new type of minocycline-induced cutaneous hyperpigmentation

Abstract: Pigmentary disorders are recognized adverse effects of the semi-synthetic tetracycline derivative antibiotic, minocycline. Three distinct types of minocycline-induced cutaneous pigmentation have been described. Type I, blue-black pigmentation confined to sites of scarring or inflammation on the face; Type II, blue-grey circumscribed pigmentation of normal skin of the lower legs and forearms; and Type III, diffuse muddy brown pigmentation of normal skin accentuated in sun-exposed areas. We report two patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 31 publications
2
59
0
Order By: Relevance
“…Cases that stain for melanin and calcium have been described. 6 Analysis of cutaneous minocycline pigmentation by mass spectroscopy indicates high levels of iron, and, to some degree, calcium. Radiographic microscopic techniques have confirmed that the clinical coloration is a result of a minocycline derivative chelated with iron that is stored within the lysosomes of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Cases that stain for melanin and calcium have been described. 6 Analysis of cutaneous minocycline pigmentation by mass spectroscopy indicates high levels of iron, and, to some degree, calcium. Radiographic microscopic techniques have confirmed that the clinical coloration is a result of a minocycline derivative chelated with iron that is stored within the lysosomes of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing cumulative dose is a risk factor for this type of discoloration, often involving collective doses of more than 100 g [15]. Tissue sections of skin stain positive for Perls' stain (indicating iron) as well as FontanaMasson stain (indicating the presence of melanin) [10,15]. Electron microscopy of these same samples demonstrates membrane-bound pigment collections.…”
Section: What Is the Clinical Spectrum Of Tetracycline-induced Skin Cmentioning
confidence: 99%
“…Since its initial use in the 1960s, there have been reports of discoloration of various body tissues in both animals and humans. Unfortunately, the insidious onset of pigmentation delays patient selfrecognition of the problem, and the variability in patterns of pigmentation encumbers physician recognition [10]. Theories explaining patterns of pigmentation include drug complexes with iron, enhancement of melanocytes, and direct oxidation of drug resulting in pigmented metabolites [11].…”
Section: What Is the Clinical Spectrum Of Tetracycline-induced Skin Cmentioning
confidence: 99%
See 1 more Smart Citation
“…This novel chromogen stains melanocytes red, which then can be differentiated from surrounding brown-colored melanin-laden keratinocytes. It has also been used in the cases to detect the micrometastases of melanoma or histopathological classification of minocycline-induced cutaneous hyperpigmentation 8,9 . Two cases of melanoacanthomas have been reported in Korean literature, but to our knowledge there is no reported case of staining using this novel chromogen VECTOR Ⓡ NovaRED TM 10,11 .…”
Section: Discussionmentioning
confidence: 99%